Pengaruh Beberapa Konsentrasi Serbuk Daun Jeruk Nipis (Citrus aurantifolia L.) Terhadap Pertumbuhan Populasi Kutu Beras (Sitophilus oryzae L.) Dan Persentase Kerusakan Beras - Sri Laisa Fitri; Tuti Heiriyani; Chatimatun Nisa (Agroekotek View, 2021)
Damage caused by warehouse pests can reduce rice quality. One type of pest that is quite important and becomes a storage constraint in warehouses is rice lice (S. oryzae) as a pest that can damage quality, resulting in economic losses. Therefore, it is necessary to find effective control methods against target pests but safe against non-target organisms and the environment. One class of pesticides that meet these requirements is pesticides derived from plants (natural pesticides). The active ingredient in lime leaves which gives a larvicidal effect, namely limonoids which work to inhibit skin turnover in larvae. Limonoids are a type of compound that is poisonous. The limonoids in lime leaf extract act as an antifeedant. This study aims to determine the effect of lime leaf powder on the population development and mortality of S. oryzae. This study used a single factor completely randomized design (CRD) experimental method consisting of six treatments including control, which was repeated 4 times in order to obtain 24 experimental units. The treatments tested were weight of lime leaf powder in 100 g of rice. Each of these treatments is A = without treatment, B = 5 g, C = 10 g, D = 15 g, E = 20 g, F = 25 g of lime leaf powder. Based on the data analysis, it was concluded that the best lime leaf powder was given to treatment F, which was 25 g, which was proven to suppress the population development of live S. oryzae by only 128 individuals. The lowest percentage of rice damage caused by S. oryzae was found in the treatment with 25 g of lime leaf powder, namely 1.73%.